2021
DOI: 10.3389/fpsyt.2021.767760
|View full text |Cite
|
Sign up to set email alerts
|

Disturbed Sleep in PTSD: Thinking Beyond Nightmares

Abstract: Sleep disturbances frequently co-occur with posttraumatic stress disorder (PTSD). Insomnia and nightmares are viewed as core symptoms of PTSD. Yet, relations between disturbed sleep and PTSD are far more complex: PTSD is linked to a broad range of sleep disorders and disturbed sleep markedly affects PTSD-outcome. This article provides a concise overview of the literature on prevalent comorbid sleep disorders, their reciprocal relation with PTSD and possible underlying neurophysiological mechanisms. Furthermore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 67 publications
0
19
0
3
Order By: Relevance
“…In contrast, other studies [ 13 , 15 ] indicated that insomnia is a predictor of PTSD. The complex relationship between insomnia and PTSD may be related to the influence of sleep on memory consolidation and emotion regulation [ 57 ]. Consequently, further studies should provide better evidence in contexts such as earthquakes and other natural disasters.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, other studies [ 13 , 15 ] indicated that insomnia is a predictor of PTSD. The complex relationship between insomnia and PTSD may be related to the influence of sleep on memory consolidation and emotion regulation [ 57 ]. Consequently, further studies should provide better evidence in contexts such as earthquakes and other natural disasters.…”
Section: Discussionmentioning
confidence: 99%
“…Emotional memory consolidation physiopathology becomes crucial in depressed (see below) and PTSD patients. Sleep complaints are virtually ubiquitous in patients with PTSD and, even if variations in the timing or amount of PS in PTSD have not been consistently found, other subtle differences in PS in PTSD are emerging, including increasing REM density and a greater PS fragmentation; moreover, abnormalities in PS activity after trauma exposure might predict subsequent development of PTSD (Lancel et al, 2021; Murkar & de Koninck, 2018). PS enhancement would bias strengthening of memories towards increased storage of negative contents, suggesting a dysfunctional attenuation of emotional tone.…”
Section: Role Of Ps In Emotional Memory and Mood Regulationmentioning
confidence: 99%
“…The vast majority of PTSD patients experience sleep disturbances, most frequently insomnia: approximately 70% report insomnia symptoms and 40% is affected by insomnia disorder [ 129 ]. Insomnia is an established risk factor for the development of and relapse in PTSD, while interventions targeting insomnia not only improve sleep quality but also ameliorate daytime PTSD symptoms [ 130 ].…”
Section: Evaluation Of Adapted Versions Of Cbt-i In Specific Mental H...mentioning
confidence: 99%